SOCIAL CAPITAL AS А FACTOR OF CLUSTER DEVELOPMENT OF А REGION - T. V. Kramin; A. S. Strelnikova (Russian Journal of Economics and Law)
Objective: to substantiate the increasing role of social capital in the development of modern clusters.Method: abstract-logical. Based on comparative analysis, the role of social capital in the functioning of clusters in different countries is studied, including by the example of leather industry.Results: the article determines that the success of cluster programs in different regions and countries depends on the role of social capital. Scientific researches are analyzed, on the basis of which it is revealed that advantages of a cluster lie in its network structure, level of trust, and interaction, which are the main components of the social capital.The theoretical studies of social characteristics of clusters are reviewed; the specificity of regional and sectoral clusters in different countries is studied. The channels of creating social capital of a cluster are illustrated within the triple helix model. The role of social capital of a cluster is proposed to be considered on the basis of cost approach.In general, the study and its results allowed drawing the following conclusion: integrated management of social capital is a promising innovative direction of cluster development under modern conditions.Scientific novelty: it is shown that cluster development requires innovations in the form of new mechanisms of social capital management. Practical significance: the main provisions and conclusions of the article can be used by regional authorities for implementing and achieving the effectiveness of their cluster programs, as well as in educational institutions in economic disciplines.